2009
DOI: 10.1038/ejcn.2009.57
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary sources and correlates of sodium and potassium intakes in the French general population

Abstract: High sodium and low potassium intakes were widespread in the population. The fact that the main dietary sources of sodium and potassium were, for the most part, not the same demonstrates the feasibility of simultaneously decreasing sodium intake and increasing potassium intake at the individual level [corrected].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
51
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 29 publications
16
51
0
3
Order By: Relevance
“…When comparing the ranking of food groups in the contribution to Na and K intakes with other studies, we observed very similar results. Bread, soup and meat products were the major sources of Na, whereas vegetables (when including potatoes), dairy products and fruit (juices) were the major providers of K, similarly to what has been described in other industrialized populations (23)(24)(25)(26)(27) . Although the contribution from water to total Na intake was not analysed in the previous surveys mentioned, it should be noted that also water can contribute to total Na intake.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…When comparing the ranking of food groups in the contribution to Na and K intakes with other studies, we observed very similar results. Bread, soup and meat products were the major sources of Na, whereas vegetables (when including potatoes), dairy products and fruit (juices) were the major providers of K, similarly to what has been described in other industrialized populations (23)(24)(25)(26)(27) . Although the contribution from water to total Na intake was not analysed in the previous surveys mentioned, it should be noted that also water can contribute to total Na intake.…”
Section: Resultssupporting
confidence: 59%
“…An important finding was the fact that our Na:K intake ratio is less than half that found in French children (26) . This lower ratio is mainly explained by lower Na intake in our Flemish pre-school children.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Since dietary habits and preferences developed in childhood and adolescence may be maintained into adulthood (2,3) , altering diet-related behaviours early in life, such as during adolescence (4,5) , is important for disease prevention. Many high-energy foods and beverages are nutrient-poor and often sources of high levels of saturated fat, sugar and salt (6) , which have been linked to overweight and obesity, dyslipidaemia, hypertension, hyperglycaemia and insulin resistance (7) . Increased intakes of high-energy foods and beverages also tend to displace consumption of more nutritious foods including fruit, vegetables and milk (8,9) , further impacting on health.…”
mentioning
confidence: 99%
“…The World Health Organization recommends that food manufacturers gradually reduce salt content in their products (World Health Organization, 2007). Among dairy products, cheese contributes to about 4% of Na intake in the United Kingdom (Ash and Wilbey, 2010), 9.2% in France (Meneton et al, 2009), and 5% in Australia (National Health and Medical Research Council, 2003). A simple reduction of NaCl without substitution with other salts adversely affects cheese quality (Reddy and Marth, 1991).…”
Section: Introductionmentioning
confidence: 99%